Transformasi Pendidikan Karakter melalui Kepemimpinan Kepala Madrasah - Lailatul Badriyah; Suwandi Suwandi (JIE (Journal of Islamic Education), 2024)
The aim of this research is to determine the school principal's leadership strategy in shaping student character education. This research uses a qualitative approach with descriptive research type. Data was obtained through interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. Data checking was carried out by testing the credibility of extending observations, increasing persistence, triangulation. The results of this research show that the school principal determines educational staff who are competent in advancing the madrasa, preparing work programs, forming curriculum preparation teams, implementing work programs, holding regular work meetings with madrasa administrators and finally evaluating work programs. Character education is carried out through habituation, example from a leader, discipline, and appropriate learning processes.